Caste, Wealth and Regional Inequalities in Health Status of Women and Children in India. Issue 1 (May 2017) - Jungari, Suresh; Chauhan, Bal Govind
Since time unmemorable, the caste system has been prevalent in Indian society. It has deeply developed roots in human minds, which leads to income inequality in the country. In the era of globalization and privatization, inequalities have extended to a large extent, which in turn has serious consequences for women and children's health. In this article, an attempt has been made to understand the Caste, Income and Regional inequalities as determinants of health of women and children. For this study, the data are derived from the National Family Health Survey III conducted during 2005–2006. Bivariate and regression analysis has been done to understand the likelihood of health status of women and child in different categories. The results show that the scheduled tribes and schedule castes having poor wealth quintile and northern Indian women and children are at a greater disadvantage in all indicators of women and child health as compared to other groups.